The placement of the spider genus Periegops and the phylogeny of Scytodoidea (Araneae: Araneomorphae) - Labarque, Facundo M.; Ramírez, Martín J. (Zootaxa, 2012)
The relationships of Scytodoidea, including the families Drymusidae, Periegopidae, Scytodidae and Sicariidae, have been con-tentious for a long time. Here we present a reviewed phylogenetic analysis of scytodoid spiders, emphasizing Periegops, theonly genus in the family Periegopidae. In our analysis the Scytodoidea are united by the fusion of the third abdominal entapo-physes into a median lobe, the presence of female palpal femoral thorns and associated cheliceral stridulatory ridges, a mem-branous lobe on the cheliceral promargin, and the loss of minor ampullate gland spigots. A basal split within Scytodoideadefines two monophyletic groups: Sicariidae and a group formed by Scytodidae as the sister group of Periegopidae plus Dry-musidae, all united by having bipectinate prolateral claws on tarsi I–II, one major ampullate spigot accompanied by a nubbin,and the posterior median spinnerets with a mesal field of spicules. Periegops is the sister group of Drymusidae, united by the regain of promarginal cheliceral teeth and a triangular cheliceral lamina, which is continuous with the paturon margin.